Is this a good time to invest in platform supply vessels? - Ho, Kennedy Wei Loong. (2012)
This paper conducts a literature review of the factors that affect an investor’s decision on purchasing various types of ships and attempts to mimic the same procedure for a Platform Supply Vessel. Similar factors were found and were analyzed using the Pearson’s Correlation Technique. Ship investment behavior was found to have a strong positive correlation with oil prices while charter rates together with exploration and production spending played a significant role in affecting an investor’s decision. Possible developments that could affect the demand of Platform Supply Vessels were also indicated and analyzed to show the prospects that lie within the industry. This study is done in hopes that an investor could use it to better time his purchase of Platform Supply Vessels in a market that is highly cyclical where the essence of time plays a very important role. Finally, a brief recommendation is done on the decision to invest in Platform Supply Vessels now.